Protection Coordination in Electrical Substation Part-2 Unit Protections (Differential and Distance Protection) -Case Study of Siddik Kardesler Substation (SKS), Istanbul, Turkey - Shobole, Abdulfetah; Baysal, Mustafa; Wadi, Mohammed; Tur, Mehmet Rida (GAZI UNIV, 2017)
Power systems must be protected against faults to ensure quality and reliable generation, transmission and distribution of power systems. Power system protection is provided by the protection relays. This paper is the second part of the Protection Coordination study for the Siddik Kardesler Substation. The protection for transmission lines, transformer, bus bars and customer feeders is provided by overcurrent protection, differential and distance protection schemes. In this paper, issues related to the Differential Protection and Distance Protection for the substation will be discussed. Finally, the test and commissioning have been conducted and the substation is successfully energized without a problem
Keywords: Differential Protection; Distance Protection; Protection Coordination; RED 615; MiCOMho P443; Science & Technology - Other Topics